On the status and selectivity of the infant burials of the Yamnaya Archaeological Culture of the Southern Urals (based on the excavation materials of the burial mound No. 1 of the Boldyrevo-4 group) - Morgunova N.L.; Faizullin A.A.; Mustafin H.H.; Alborova I.E.; Kiseleva D.V.; Chechetkina O.Yu.; Mednikova M.B. (Вестник археологии, антропологии и этнографии, 2023)
Bioarchaeology is an important field of interdisciplinary research based upon the contextual study of anthropological materials. In particular, bioarchaeology of childhood appears to be the most specialised area of research, addressing quality of life and social patterns of ancient groups. In this paper, we continue the study of the infant remains from the burial mound No. 1 of the Boldyrevo-4 burial ground — one of the elite and largest burial mounds of the Yamnaya (Pit Grave) Culture in the northern part of the Volga-Urals. It was located on the left bank of the Irtek River, a tributary of the Ural, and had a diameter of 62 m and a reconstructed height of 8 m. The earliest horizon was represented by mounds Nos. 1 and 2 with close parameters. They contained one burial each (burials Nos. 3 and 4, respectively), located in the centers of the mound platforms, which belonged to children. Based on the results of our preliminary study, the child from burial No. 3 died of metastatic cancer (the most probable diagnosis is lymphocytic leukaemia). Burial No. 4 contained remains of two children. Child No. 1 from burial No. 4, represented only by the cranium, had possibly suffered from scurvy. Here we publish the results of the analysis of ancient DNA aimed at identifying the sex of the interred, as well as the results of the Sr isotope analysis, which allows determination of their ‘local’ or ‘distant’ origin. The quality of the ancient DNA was evaluated by targeted sequencing carried out using a specially designed panel of probes that allowed the selection of target sections of the genome for subsequent enrichment using the method of hybridisation, followed by the target NGS. The genetic data confirm that all three individuals belonged to the female sex. On the basis of Sr isotope ratios, the girls from burials Nos. 3 and 4 (No. 2) were born in the territories with different geochemical signals. Unfortunately, for the child No. 1 from burial No. 4 such observations could not be obtained. The biological age (around 6 years old), female sex attributes, and the presence of serious health conditions allows one to pose the question on the selective nature of the children burials in this mound of the Yamnaya Culture. Moreover, they could have received a special hereditary social status, which influenced the further erection of the burial mound for members of the elite.